Characterization of WOX genes revealed drought tolerance, callus induction, and tissue regeneration in Gossypium hirsutum - Muhammad Tajo, Sani; Pan, Zhaoe; He, Shoupu; Chen, Baojun; KM, Yusuf; Mahmood, Tahir; Bello Sadau, Salisu; Shahid Iqbal, Muhammad; Gereziher, Teame; Suleiman Abubakar, Umar; Joseph, Masha; Sammani, Tajo; et al. (Frontiers in Genetics, 2022)
Cotton is an important natural fiber crop; its seeds are the main oil source. Abiotic stresses cause a significant decline in its production. The WUSCHEL-related Homeobox (WOX) genes have been involved in plant growth, development, and stress response. However, the functions of WOX genes are less known in cotton. This study identified 39, 40, 21, and 20 WOX genes in G. hirsutum, G. barbadense, G. arboreum, and G. raimondii, respectively. All the WOX genes in four cotton sepecies could be classified into three clades, consistent with previous research. The gene structure and conserved domain of all WOX genes were analyzed. The expressions of WOX genes in germinating hypocotyls and callus were characterized and found that most genes were up-regulated. One candidate gene Gh_ A01G127500 was selected to perform the virus-induced gene silencing (VIGS) experiment and found that the growth of the silenced plant (pCLCrVA: GhWOX4_A01) was significantly inhibited compared with the wild type. In the silenced plant, there is an increase in antioxidant activities and a decrease in oxidant activities compared with the control plant. In physiological analysis, the relative electrolyte leakage level and the excised leaf water loss of the infected plant were increased. Still, the relative leaf water content and the chlorophyll content were both decreased. This study proved that WOX genes play important roles in drought stress and callus induction, but more work must be done to address the molecular functions of WOX genes.